Music's AI Problem, AI's Music Problem. - White, Christopher W. (Journal of the American Musicological Society)
The article examines the development and implications of artificial intelligence (AI) in music, focusing on generative musical AI, its technical foundations, and its cultural and creative impact. Topics include the history of musical AI, machine learning and neural networks, and the capacities and limitations of AI-generated music.